A PHARMACOECONOMIC STUDY IN TWO TERTIARY CARE HOSPITALS IN ABBOTTABAD - Khattak, Safeer Khan; Mehsud, Saif Ullah; Haider, Irfan Zafar; Burki, Musarrat Rauf (Journal of Ayub Medical College Abbottabad, 2012)
Background: Pharmacoeconomics has been defined as: the description and analysis of the cost of drug therapy to health care systems and society. Aim was to observe the Medication Therapy on the basis of Phamacoeconomics Analysis and to save the economic resources. Methods: This Descriptive Cross sectional study was conducted at Ayub Teaching Hospital and Combined Military Hospital, Abbottabad, from May-August 2011. The case histories of 100 patients were scrutinized thoroughly specially with reference to socioeconomic history, Clinical laboratory tests, Medication history and treatment at hospital and discharge medications. After their collection, these case histories were analyzed with respect to Phamacoeconomics and compared with the world literature. Result: A total of 100 patients were studied. Pharmacoeconomic analysis shows that in 49 Patients’ medications were according to international standards while in 51 patients’ medications prescribed were irrational. Conclusion: Mutual interaction between physician, surgeon, other healthcare professionals, and clinical pharmacist is necessary to assure rational medication therapy and positive response to therapy of each patient. Keywords: Pharmacoeconomics, Rational Therapy